2008
DOI: 10.1073/pnas.0805566105
|View full text |Cite
|
Sign up to set email alerts
|

Light, nutrients, and food-chain length constrain planktonic energy transfer efficiency across multiple trophic levels

Abstract: The efficiency of energy transfer through food chains [food chain efficiency (FCE)] is an important ecosystem function. It has been hypothesized that FCE across multiple trophic levels is constrained by the efficiency at which herbivores use plant energy, which depends on plant nutritional quality. Furthermore, the number of trophic levels may also constrain FCE, because herbivores are less efficient in using plant production when they are constrained by carnivores. These hypotheses have not been tested experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
212
5
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(232 citation statements)
references
References 31 publications
(49 reference statements)
14
212
5
1
Order By: Relevance
“…Stoichiometric arguments based on light and nutrient levels indicate that while increases in light at low irradiance levels may increase phytoplankton biomass and thus zooplankton growth, high light levels may reduce the nutritional quality of phytoplankton for higher trophic levels (Urabe and Sterner 1996;Dickman et al 2008). Two important consequences of this are that more transparent lakes have lower food quality (higher carbon : phosphorus [C : P]) in the surface waters (Sterner et al 1997) and that the food in the DCM is likely to be of higher nutritional quality than that in the surface waters (Rothhaupt 1991).…”
mentioning
confidence: 99%
“…Stoichiometric arguments based on light and nutrient levels indicate that while increases in light at low irradiance levels may increase phytoplankton biomass and thus zooplankton growth, high light levels may reduce the nutritional quality of phytoplankton for higher trophic levels (Urabe and Sterner 1996;Dickman et al 2008). Two important consequences of this are that more transparent lakes have lower food quality (higher carbon : phosphorus [C : P]) in the surface waters (Sterner et al 1997) and that the food in the DCM is likely to be of higher nutritional quality than that in the surface waters (Rothhaupt 1991).…”
mentioning
confidence: 99%
“…Durant et al (2005) showed that food resources and consumer levels also determine the strength of PZC. Other characteristics that have been identified to qualitatively affect the strength of PZC include food quality (Dickman et al 2008), phytoplankton taxonomic composition (Auer et al 2004), zooplankton diversity (McCann et al 1998), alternative food resources such as microphytobenthos or microbial communities (Rautio and Vincent 2006), and zooplankton predators (Hessen et al 2006;Dickman et al 2008). All of these might be influenced by global stressors.…”
mentioning
confidence: 99%
“…Aquatic invertebrates, particularity those that bioturbate sediments, alter the flux of nutrients into water , Palmer et al 2000. Changes in nutrient concentrations may lead to changes in the efficiency of energy transfer through food chains (Dickman et al 2008). Additionally, changes in nutrient concentrations may influence other ecosystem functions such as primary production and decomposition, as identified in this study ( Palmer et al 2000).…”
Section: Carbamazepine Influence On Ecosystem Dynamicsmentioning
confidence: 99%